METODE PEMBELAJARAN PENDIDIKAN ISLAM UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Nurrita, Teni; Ikrom, Muhammad (Moderation | Journal of Islamic Studies Review, 2022)
Learning methods play an important role in achieving the goals or success of teaching according to the level of education and age of students. Teachers can provide learning methods to students in a simple but interesting way and are able to increase learning motivation so that the learning atmosphere in the classroom becomes fun. Teachers are expected to be able to choose and use dynamic learning methods by observing students' conditions before learning. To use learning methods can be based on learning objectives, types of activities, student circumstances, teacher skills, situations and conditions, available facilities and the goodness or weakness of a learning method. The learning method is the method used to develop plans for real activities so that the learning objectives that have been set optimally can be achieved. Islamic education is an activity carried out to develop all human potential by guiding humans to become believers who are physically, mentally and spiritually strong and intelligent, have noble character and are useful, both for their own needs and for others. Learning motivation is a condition in the individual that encourages him to study seriously to achieve goals that will shape student behavior for the better. The types of learning methods include: lecture method, demonstration method, discussion method. Learning methods that can be used in Islamic education include: lecture method, discussion method, question and answer method, exemplary/imitating method. Increased student motivation can be seen from several things, namely: students dare to ask the teacher in class, students dare to answer questions, students dare to answer questions, students dare to express opinions, students do assignments seriously